MAKROPOLITYCZNE UWARUNKOWANIA KULTURY SZKOLNEJ - Śliwerski, Bogusław (Rocznik Pedagogiczny, 2018)
The subject of the article is the involvement of the school’s culture in the centralistic education policy, which is led by all, successively changing governments. It started with systemic reform of educational system in 1999. The author pays attention to the extent to which such a policy destroys the innovativeness of teachers. The only solution to this situation is the return to the anti-systemic micro-innovation movement in public education due to it restores the sense of dignity and profes- sional self-fulfillment of teachers.